Dynamic Behavior of Geosynthetic-Reinforced Expansive Soil under Freeze-Thaw Cycles - Zhongnian Yang; Xuesen Liu; Liang Zhang; Fujun Niu; Xianzhang Ling; Guoyu Li; Wei Shi (Advances in Civil Engineering)
Expansive soil has a significant impact on the stability of many key construction projects in cold regions. To study the physical and mechanical properties of expanded soil under the condition of freeze-thaw cycle, cryogenic cyclic triaxial tests were conducted on the dynamic and the displacement characteristics of geosynthetic-reinforced expansive soil subjected to the freeze-thaw cycles. Compared with the unreinforced expansive soil samples, the effects of freeze-thaw cycles on the soil dynamics were discussed. The dynamic shear modulus (Gd) and damping ratio (λ) of the expansive soil samples are improved by reinforcement. Reinforced soil can inhibit the axial compression of the sample and restrain the frost heave deformation of the sample during the freezing process. Meanwhile, it can delay the structural damage effect caused by frost heave and reduce the rate of change of the Gd and the λ with the freeze-thaw cycle. At the same time, reinforced soil can inhibit the axial expansion, reduce the rate of reduction of the Gd, stabilize it with a higher rate, and reduce the influence of the freeze-thaw cycles on the λ of the expansive soil sample. Finally, the change of mechanical properties of expansive soil under the condition of reinforcement is obtained. The main conclusions of this paper can be used to reinforce the roadbed and foundation engineering of frozen soil in a cold region and provide support for the fiber reinforcement method of expansive soil.